2018
DOI: 10.1186/s12887-018-1243-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hemofiltration improves the prognosis of bacterial sepsis complicated by liver dysfunction in children

Abstract: BackgroundLiver dysfunction is an independent risk factor for poor prognosis of patients with sepsis. The aim of this study is to evaluate the effects of continuous hemofiltration in patients with bacterial sepsis complicated by liver dysfunction.MethodsWe retrospectively analyzed the medical records of 27 cases of bacterial sepsis with liver dysfunction admitted to pediatric intensive care unit (PICU) of Shanghai Children’s Hospital between January 2013 and December 2016.Results28-day mortality and length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
1
1
Order By: Relevance
“…In a recent study, it was shown that continuous haemofiltration significantly improves mortality in paediatric patients with bacterial sepsis-associated liver dysfunction [18]. In contrast to that study, we did not find a significant improvement in ALT levels with CRRT alone.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study, it was shown that continuous haemofiltration significantly improves mortality in paediatric patients with bacterial sepsis-associated liver dysfunction [18]. In contrast to that study, we did not find a significant improvement in ALT levels with CRRT alone.…”
Section: Discussioncontrasting
confidence: 99%
“…403), implying that the application of CVVHDF might contribute to the decreased tendency in mortality. In our previous study, CVVHDF showed clinical benefits in the management of severe sepsis, sepsis-associated hemophagocytic lymphohistiocytosis, and sepsis-associated liver injury in our PICU [1214, 21]. The current study focused on CVVHDF empiric therapy for severe EV-A71-HFMD, as CVVHDF has been a recommend therapy for severe pediatric EV-A71-HFMD complicated by cardiopulmonary failure in the 2018 Guideline for HFMD in China [4].…”
Section: Discussionmentioning
confidence: 99%
“…Hemofiltration is useful in curtail the adverse effects of infections in infants and aged patients. It was found to reduce the serum levels of bile acid microbial metabolites namely, total bilirubin, direct bilirubin, total bile acids, lactate and IL-6 in patients suffering from bacterial sepsis and hepatic dysfunction ( Cui et al, 2018 ). Various devises are available in markets for hemofiltration.…”
Section: Hemofiltration Devicesmentioning
confidence: 99%